Pengaruh perhatian orang tua, self-efficacy, dan motivasi terhadap hasil belajar matematika siswa - Enda Imelda; Syamsuri Syamsuri; Novaliyosi Novaliyosi (TIRTAMATH: Jurnal Penelitian dan Pengajaran Matematika, 2022)
Abstract: This study aims to obtain a structural equation model related to the variables of parental attention, self-efficacy, and motivation on the mathematics learning outcomes of MTs students. Knowing the influence and contribution of parental attention, self-efficacy and motivation to the mathematics learning outcomes of MTs students. This study is a quantitative study with a survey method that aims to determine the structural equation model related to the variables of parental attention, self-efficacy, and learning motivation on the mathematics learning outcomes of MTs students. The results of the study revealed that parental attention, self-efficacy and learning motivation had a positive and significant influence on MT students' mathematics learning outcomes. -have predictive values of 0.315 ( t = 6.685, p = 0.000), 0.439 ( t = 8054, p = 0.000) and 0.196 ( t = 4.013, p = 0.000). The contribution given by parents' attention, self-efficacy of learning motivation has a positive and significant influence on learning outcomes by 82.20%, the rest is influenced by factors not contained in this study.